Factors Contributing to Poor Performance of Grade 4 Learners in English Second Language - Andreas, Elizabeth Thapadhi; Kamati, Ferdinand Nghifikepunye (Papanda Publisher, 2024)
The study aimed to investigate the factors that contribute to the poor performance of Grade 4 learners in English at three selected primary schools in the Oshikoto Region in Namibia. The qualitative approach was adopted in the form of a case study design. The data were collected through a semi-structured interview and document analysis. A sample comprising six (6) English teachers was chosen using purposive sampling. The data were analyzed using a thematic analysis approach. The study revealed that contributing factors to poor performance were language barriers, lack of resources, lack of motivation, and lack of training and workshops. The study recommends that the Ministry of Education, Arts, and Culture should provide teaching and learning resources, organize and offer workshops to teachers, and monitor compensatory programs.